Modulating transcription factor activity: Interfering with protein-protein interaction networks. (March 2020) - Francois, Mathias; Donovan, Prue; Fontaine, Frank
Abstract: Biophysical parameters that govern transcription factors activity are binding locations across the genome, dwelling time at these regulatory elements and specific protein-protein interactions. Most molecular strategies used to develop small compounds that block transcription factors activity have been based on biochemistry and cell biology methods that that do not take into consideration these key biophysical features. Here, we review the advance in the field of transcription factor biology and describe how their interactome and transcriptional regulation on a genome wide scale have been deciphered. We suggest that this new knowledge has the potential to be used to implement innovative research drug discovery program.